(untitled) (Balneo and PRM Research Journal, 2021)
Introduction. Currently, the crises triggered by the pandemic, in the fields of health, freedom of movement, economic, with impact in the social and cultural spheres, bring back today the practical applicability of the concepts of fitness and wellness. Material and method. In our study we will refer to the effects of the pandemic on health (everyone’s well-being), to see how they accentuated the negative effects of the risks that specialists linked to sedentary lifestyle; increased stress; static anti-physiological positions for prolonged periods of time, which result in cardiovascular disease, metabolic syndrome and even cancer, to which is added an irrational diet. We will also refer to the relationship between the quality of life of people and the need to find the most effective ways to combat the negative effects of risk factors, by overcoming the obstacles posed by the financial situation and cultural patterns both in terms of lifestyle, as well as the eating behavior of people from different backgrounds. Results and discussions. We are of the opinion that specialists must go in their approaches, from the cultural understanding of man, to find ways to individualize the means of intervention so as to achieve the proposed objectives. The framework could be, for children and adolescents - the reorganization of school physical education, and for young people and adults - leisure activities, in which the emphasis could be falls on the concepts of Fitness and Wellness, with a beneficial effect on quality of life and personal satisfaction. Conclusion In this context, we believe that it is necessary to reconsider the need to make the population aware of the formation of a healthy lifestyle. The means could be physical fitness, wellness, rational nutrition and recovery according to the effort made, their benefits can have a major impact on health and prolong life expectancy.